Independence of Local Government in the Comfortable Cities of the World - S. V. Bogachov; M. R. Pinskaya (Управленческие науки)
The paper is devoted to the study of a local governments’ role in ensuring the life quality of the population in cities with a high comfort rating. The purpose of the research is a detection of similarities and differences in the organizational, legal and financial components of local governments in solving the problem of increasing the level of comfort in urban life. As an object of the research is testing a hypothesis about what aspects of an autonomy of local governments (legal, organizational acts or financial) are dominant in ensuring the life quality in cities.The methodology of the work is based on a systematic approach, which allows to reveal problems of financial support for the activities of local governments, aimed at improving the life quality of the population. Ratings of the world cities on comfort level are considered, selection of twenty cities are having high rating of comfort according to consulting agency Mercer is defined (further — the cities of «the comfortable twenty») and their group over the countries is executed. The analysis of legal, organizational and financial autonomy of local government bodies in the cities of “the comfortable twenty” is carried out.On analysis results the conclusion is drawn on sufficient degree legal autonomy (powers), organizational independence and financial independence of local government bodies that in combination with stability of the legislation on a local self-government allows to provide the high level of life quality of the population in the cities of “the comfortable twenty”. The conducted research is urged to fill the existing gaps between theoretical ideas of powers of local government bodies and the practical analysis of a real problem condition of increasing the effective management of cities due to strengthening of the financial independence of municipal authorities.